Narrative Polyphony in Novel “Savely’s Days” by G. Sluzhitel - O. I. Osipova (Научный диалог, 2021)
The narrative structure of the novel “Savely’s Days” by G. Sluzhitel is considered. It is determined that a polyphonic system of narrative instances is expressed in the novel, and the relationship between them is established. Methods of creating a subjective versatility of the text have been studied. It is noted that the genre of memories as a whole retains constant features, which include the methods of creating a chronotope. It embodys the image of a hero, while it is the very feature of the protagonist, who is an unreliable narrator, that leads to the transformation of the classical narration of memories and to the emergence of several subject-speech plans. The relevance of the study is due to the need to study the narrative instances and the originality of their relationship in order to comprehend the narrative space of a work of art. The novelty is seen in the fact that the methods of creating the effect of polyphonic narration are determined on the basis of the material of the modern novel. The observation of the modern writer style formation is carried out. It has been proved that the polyphony of narrative images arises in the novel due to the fact that, technically, the story cannot be conducted only from the point of view of the cat-narrator, since this will significantly limit the discourse. The purpose of polyphony is to look at a modern person from different points of view, including a detached one.